2005
DOI: 10.1299/jsmeb.48.687
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Stratified Charge for DISI Engines through Split Injection(Effect and Its Mechanism)

Abstract: The effect of split injection on the mixture characteristics of DISI (Direct Injection Spark Ignition) engines was investigated firstly by the Laser Absorption Scattering (LAS) technique. Through splitting the fuel injection process, two possible benefits were found: 1) High density liquid droplets piling up at the leading edge of the spray can be circumvented, subsequently the reduction of the spray tip penetration; 2) The quantity of "over lean" (φ v < 0.7, φ v : equivalence ratio of vapor) mixture in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Such findings are not uncommon and indeed other studies of split injections for DISI engines have also reported improved air entrainment, mixing and evaporation [28]. Spray-gas momentum transfer is considered critical for defining spray structure and driving the efficiency of mixture preparation process.…”
Section: °C 90 °Cmentioning
confidence: 85%
“…Such findings are not uncommon and indeed other studies of split injections for DISI engines have also reported improved air entrainment, mixing and evaporation [28]. Spray-gas momentum transfer is considered critical for defining spray structure and driving the efficiency of mixture preparation process.…”
Section: °C 90 °Cmentioning
confidence: 85%
“…Stable and smooth combustion without knocking could be possible with optimized proportions of the two-stage injection, while soot was not detected. The evaporation of the second amount of injected fuel is promoted by the ambient air motion in the tail region of first fuel spray [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of split injections with multi-hole injectors for DISI engines have reported improved air entrainment, mixing and evaporation under late injection strategies for stratified operation, e.g. [14,15]. It needs to be noted though that the main characteristic of multi-hole injectors is that they produce very robust spray plumes consisting of individual vapour branches rather than forming a complex cloud structure.…”
Section: Split-injection Strategies For Spark-ignition Enginesmentioning
confidence: 99%